PROSPECTS FOR THE DEVELOPMENT OF ISLAMIC BANKING SERVICES MARKET IN COMMERCIAL BANKS OF UZBEKISTAN - Kayimova Z.A. (Scholar Express Journals, 2021)
This scientific article discusses the differences between Islamic banking products and services from traditional banking services, as well as their advantages and the main reasons for the growing interest. It also provides information on the first steps in the development of the Islamic banking market in Uzbekistan. The sufficiently intensive development of Islamic banking is due to the growing demand and the significant accumulation of financial resources by Muslim countries. Given the active development of financial markets in the Arab world and the competition among Western companies to attract foreign investors, it can be said that the growth trend of Islamic banks will continue. This sets out the necessary conditions for a more comprehensive analysis of the activities of Islamic banks, as well as to determine their access to financial markets.
Keywords: Islamic bank; mudoraba; musharaka; rent